Systemic sclerosis-related calcinosis. Issue 2 (May 2016) - Herrick, Ariane L.; Gallas, Andrzej
Purpose: To provide an update on the clinical burden of calcinosis (subcutaneous or intracutaneous deposition of calcium salts) in patients with systemic sclerosis (SSc), and discuss advances in our understanding of pathogenesis, associates, and measurement techniques, as well as an overview of the current approach to management. Methods: Four case scenarios are presented, to illustrate the clinical spectrum of calcinosis. Epidemiology (including associates), pathogenesis, imaging and measurement, and treatment are reviewed. Results: Calcinosis represents a major clinical problem in patients with SSc. Up to 40% of patients are affected, the proportion depending in part on how carefully calcinosis is looked for. Associates of calcinosis include longer disease duration, anticentromere antibody, and digital ulceration. When severe, calcinosis causes pain, disability, and disfigurement. Pathogenesis is unknown, but tissue ischaemia, microtrauma, and loss of balance between calcification stimulants and inhibitors are likely contributors. Calcinosis deposits are mainly composed of hydroxyapatite. They are very visible on plain radiographs, and radiographic scoring systems are being developed, and other imaging modalities (including computed tomography and ultrasound) are being explored. Despite a number of proposed treatments, currently there is no effective 'disease-modifying' therapy for calcinosis and the main aspects of management are antibiotics, analgesics, multidisciplinary team input, and surgical debulking. Conclusions: Up until recently, SSc-related calcinosis has received very little attention in terms of research into pathogenesis, measurement, and treatment. This imbalance is now being redressed and although we still do not have an effective treatment, progress is being made.